Management of chronic constipation in comorbid conditions - Bagepally, Ravi Shankar (International Journal of Research in Medical Sciences, 2022)
Constipation is a common clinical problem in India. It is also a secondary condition in many disorders. This article focused on clinical assessment and evidence-based treatment options for managing chronic constipation in various disorders. A literature search of published medical reports in the English language was performed using PubMed from inception to 2021. The selected articles satisfied the following inclusion criteria: involved human subjects over the age of 18 years and reported at least one of the comorbidities among hypothyroidism, diabetes and hypertension along with chronic constipation. Chronic constipation is one of the most common gastrointestinal symptoms observed in patients with diabetes, hypertension or hyperthyroidism. Constipation in diabetic patients can occur due to several factors such as autonomic dysfunction, dietary habits and medications. The change in the intestinal microbiota because of chronic constipation can also induce cardiovascular events. The association between these changes and increased blood pressure resulting in hypertension had been discussed in this review. Additionally, the link between disturbed gastrointestinal motility and chronic constipation leading to hypothyroidism had also been explored. Furthermore, the pharmacological and non-pharmacological management of chronic constipation in patients with diabetes, hypertension, and hypothyroidism have been discussed. Emphasis has been placed on the changes required in the existing treatment options for diabetes, hypertension and hypothyroidism along with the use of laxatives, dietary fibers, bulking agents, lifestyle changes and other interventions to manage chronic comorbid constipation.